Homework? (Journal of Parents and Teachers, 2014)
Talking about homework or homework has become a taboo subject. It is necessary to avoid that the duties put in tension to the students and, for that, it is necessary to select activities according to the needs of the students, and not those of the teacher. The article raises the criteria that must have a task to be appropriate as duties and not to be used as a "patch of cracks" that ends with the motivation of children.
Keywords: Homework; taboo; utility; reflection; flexibility; coordination; evaluation